2023
DOI: 10.3390/cancers15082391
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus Video-Assisted Thoracic Surgery for Lung Cancer: Short-Term Outcomes of a Propensity Matched Analysis

Abstract: Robot-assisted thoracic surgery (RATS) has gained popularity for the treatment of lung cancer, but its quality outcome measures are still being evaluated. The purpose of this study was to compare the perioperative outcomes of lung cancer resection using RATS versus video-assisted thoracic surgery (VATS). To achieve this aim, we conducted a retrospective analysis of consecutive patients who underwent lung cancer surgery between July 2015 and December 2020. A propensity-matched analysis was performed based on pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…Our findings align with a study by Lampridis et al in 2023, which showed that the transfusion requirement rate in lung cancer patients undergoing resection with the robotic procedure was lower than that in VATS, although not significantly different {95% CI, −3.1 (−7.3, 1.2) P 0.161}. However, there was a significant difference in the estimated blood loss parameter, with RATS being lower by 87.5 mL compared to VATS (95% CI, 48.1 to 126.8 mL; p < 0.001) (Lampridis et al, 2023). The results of the meta-analysis regarding the parameter of surgical duration show no significant difference between robotic and VATS procedures (OR 12.57, 95% CI (-6.64, +31.78)), with high heterogeneity (I2: 97%; p < 0.0001).…”
Section: Discussionmentioning
confidence: 83%
“…Our findings align with a study by Lampridis et al in 2023, which showed that the transfusion requirement rate in lung cancer patients undergoing resection with the robotic procedure was lower than that in VATS, although not significantly different {95% CI, −3.1 (−7.3, 1.2) P 0.161}. However, there was a significant difference in the estimated blood loss parameter, with RATS being lower by 87.5 mL compared to VATS (95% CI, 48.1 to 126.8 mL; p < 0.001) (Lampridis et al, 2023). The results of the meta-analysis regarding the parameter of surgical duration show no significant difference between robotic and VATS procedures (OR 12.57, 95% CI (-6.64, +31.78)), with high heterogeneity (I2: 97%; p < 0.0001).…”
Section: Discussionmentioning
confidence: 83%